Pengaruh Penggunaan Media Sosial Facebook terhadap Rendahnya Komunikasi Interpersonal antar Remaja - Razak, Fandriyati; Hastuti, Hastuti; Ardiansah, Muh. Rizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the relationship between the use of Facebook social media and low interpersonal communication among adolescents in Todanga Village, Kapontori District. The method in this study uses quantitative research. The results of the study indicate that there is a strong relationship between the use of Facebook and low interpersonal communication, with a correlation coefficient value of 0.598, by the interpretation of the correlation coefficient value of 0.50-0.75 which is considered strong. The contribution of Facebook use to low interpersonal communication reaches 74.7%, while 25.3% is influenced by other variables not examined in this study. The t-test shows that the use of Facebook has a significant effect on low interpersonal communication among adolescents in Todanga Village, which means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, there is a significant influence of the use of Facebook social media on low interpersonal communication. Keywords: Todanga Village, Kapontori District, Interpersonal Communication Between Adolescents, Use of Facebook Social Media